Transcranial direct current stimulation to prevent and treat surgery-induced opioid dependence: a systematic review. (5th December 2018) - Gallucci, Alessia; Lucena, Pedro H; Martens, Géraldine; Thibaut, Aurore; Fregni, Felipe
Opioid misuse leading to dependence is a major health issue. Recent studies explored valid alternatives to treat pain in postsurgical settings. This systematic review aims to discuss the role of transcranial direct current stimulation (tDCS) in preventing and treating postoperative pain and opioid dependence. PubMed and Embase databases were screened, considering studies testing tDCS effects on pain and opioid consumption in surgical settings and opioid addiction. Eight studies met our inclusion criteria. Results showed a reduction of postoperative pain, opioid consumption and cue-induced craving following cortical stimulation. Despite the limited number of studies, this review shows preliminary encouraging evidence regarding the analgesic role of tDCS. However, future studies are needed to further investigate the application of tDCS in postsurgical settings.